Nutrition-related knowledge, perceptions, and practices of caregivers with galactosaemic infants and children following a therapeutic diet in the United Kingdom - Blaauw, Giana Francis (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNutr)--Stellenbosch University, 2023.